Pengaruh Disiplin Kerja dan Motivasi Kerja terhadap Kinerja Karyawan pada PT. Exabb Energy Nusantara - Abdullah, Abdullah; Noviyanti, Iis; Kristianti, Lily Setyawati; Asmalah, Lia (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
In the current competitive business environment, understanding the factors that influence employee performance is essential for organizations to enhance their productivity and overall success. This study aims to investigate the impact of employee discipline and motivation on employee performance at PT. Bank Index Selindo KC. Pluit. The research utilizes a quantitative approach, and data processing is performed using statistical analysis. The sample size was determined using Slovin's formula with a 5% margin of error, resulting in 109 respondents. The data analysis methods include validity tests, reliability tests, classical assumption tests, autocorrelation tests, regression analysis, t-tests, F-tests, and the coefficient of determination. The results of the analysis indicate that employee discipline does not have a significant impact on performance when examined independently, while motivation has a positive and significant effect on employee performance. Furthermore, both employee discipline and motivation, when considered together, significantly affect employee performance. These findings suggest that motivation plays a key role in improving employee performance, while discipline alone may not be as influential. Organizations should focus on strategies to enhance motivation to achieve better performance outcomes.